U'Ductor: A Model for Supporting Ubiquitous Chronic Disease Care Management - Viana, Henrique; Barbosa, Jorge; Costa, Cristiano; Yamin, Adenauer C. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2012)
Accordingly with the World Health Organization, heart disease, chronic respiratory diseases, cancer and diabetes are the most common chronic diseases and one of the leading causes of the mortality in the world. In such cases we need more than patient engagement to help to control of the disease, community and health organizations support is also desirable. These roles must support the patients' self-management activities, making them feel confident and motivated. This support can be accomplished by ubiquitous computing. The ubiquitous computing gives conditions to help chronic diseases patients in the management of their activities, offering support to them anytime, anywhere. In this context, this article presents U'Ductor, a model for supporting ubiquitous chronic care management, whose goal is to help the integration between patient and community resources. The U'Ductor gives a step forward in relation to the studied related works by integrating patients, community resources and community members. Those features were not completely explored in the studied works in the way we employ in U'Ductor. An implementation of the model was evaluated by a chronic patient, which gave a positive feedback about it.